Pengaruh Strategi Promosi, Persepsi Risiko, dan Persepsi Harga Jual Kembali Terhadap Minat Berinvestasi Emas pada PT Pegadaian Cabang Dompu - Widia Ningsih; Yeye Suhaety; Lilis Marlina (JURNAL RISET MANAJEMEN (JURMA), 2026)
This study examines the partial and simultaneous effects of promotional strategies, risk perception, and resale price perception on public interest in gold investment at PT Pegadaian Dompu Branch. The research employed a quantitative explanatory approach involving 96 respondents selected from a population of 50,000 customers using purposive sampling. Data were collected through a structured questionnaire based on a five-point Likert scale and analyzed using multiple linear regression with SPSS version 26. The findings reveal that promotional strategies have a positive and significant influence on public interest in gold investment, indicating that effective promotional activities encourage customers to invest. Risk perception also shows a positive and significant effect, suggesting that customers with better understanding and management of investment risks are more inclined to invest in gold. In addition, resale price perception positively and significantly affects investment interest, reflecting the importance of customers' confidence in obtaining favorable resale values. Simultaneous testing using the F-test confirms that the three independent variables jointly have a significant effect on public interest in gold investment. The coefficient of determination shows an Adjusted R Square value of 33.9%, meaning that promotional strategies, risk perception, and resale price perception explain 33.9% of the variation in investment interest, while the remaining 66.1% is influenced by other factors not included in this research model.